Palm Juice Transactions for Making Alcoholic Beverages from the Perspective of KHES and the Civil Code in Tanjung Beringin District - Tengku, Faqih; Harahap, Mhd. Yadi (AJIS: Academic Journal of Islamic Studies, 2024)
Trade and commerce are essential to the economic activities of society, encompassing the exchange of goods or services with the purpose of deriving economic advantages. Within the framework of Indonesian law, these transactions are governed not only by civil regulations but also by Sharia principles, especially concerning adherence to religious and ethical standards.This study aims to examine the legal standing of transactions involving palm sap (nira water) utilized in the production of alcoholic beverages, viewed through the lenses of KHES and KUHP in Tanjung Beringin Subdistrict, Serdang Bedagai Regency. This study adopts an empirical juridical research method, employing a qualitative approach with comparative analysis. The research utilizes both primary and secondary sources of data, gathered through techniques such as observations, interviews, and document analysis.The study concludes that, under KHES, transactions involving palm sap intended for manufacturing alcoholic beverages are classified as invalid (fasid). This is due to the prohibition of alcoholic beverages in Sharia law, which renders any transaction related to palm sap for this purpose defective, regardless of whether it meets the formal requirements and conditions of a legitimate sale. As such, these transactions are subject to annulment. Conversely, from the perspective of the Indonesian Civil Code (KUHP), such transactions are deemed legally valid, as there is no specific prohibition against the trade of palm sap for producing alcoholic beverages within its provisions. Consequently, the transfer of ownership and rights from the seller to the buyer is recognized as lawful under civil law.